Edukasi Pemanfaatan Tanaman Obat Menjadi Racikan Tradisional dalam Upaya Pencegahan Covid-19 di Desa Tolongio - Hula, Ibnu Rawandhy N; Ibrahim, Sulaiman; Fadilah Kaaba, Nanda; Rauf, Ningsi C. (Madani: Jurnal Pengabdian Ilmiah, 2021)
The focus of this research is on educating medicinal plants that come from natural ingredients, traditionally formulated by community groups, and are believed to have efficiencies in increasing immunity to prevent Covid-19 transmission during the Pandemic for people in the Anggrek sub- district. This research method uses descriptive qualitative method with four stages, namely identification, planning, action and evaluation. The identification stage is carried out by observing to obtain initial data regarding the public's understanding of medicinal plants, as well as the technicality of mixing them so that they become alternative medicines in the prevention of Covid-19. At the planning stage, researchers compiled a schedule and material for medicinal plants in the form of leaflets. Furthermore, at the action stage, it is carried out by providing education about the types of medicinal plants and how to mix them which is carried out through education and online discussions. In the final stage, an evaluation was carried out by distributing an online questionnaire, using a Likert scale, in order to determine their response and increase their understanding of the variety of traditional medicinal plants that are useful in increasing immunity and preventing the spread of Covid-19. The results of this study indicate that there is an increase in public understanding after participating in online educational activities, that public knows the types of medicinal plants and their benefits, namely Very Understanding = 25%, Understanding = 50%, Doubting = 16.7%, Lack of Understanding = 8.3% and Not Understanding = 0%. 2) People understand how to process medicinal plants those are, very understanding = 8.3%, understanding = 50%, doubt = 33.3%, lack of understanding = 8.3% and not understanding = 0%.